2009
DOI: 10.1111/j.1365-2184.2008.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Myc down‐regulation affects cyclin D1/cdk4 activity and induces apoptosis via Smac/Diablo pathway in an astrocytoma cell line

Abstract: Our results suggest that c-Myc could be considered as a good target for the study of new approaches in anticancer astrocytoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
(80 reference statements)
2
16
0
Order By: Relevance
“…Likewise, we demonstrated this in two previous reports, as the modulation of this oncogene can also sensitize cells towards apoptosis in response to cytotoxic insults including chemotherapeutic agents and radiotherapy (38,39).…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, we demonstrated this in two previous reports, as the modulation of this oncogene can also sensitize cells towards apoptosis in response to cytotoxic insults including chemotherapeutic agents and radiotherapy (38,39).…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that TGF-β down-regulates transcription factors involved in proliferation such as c-Myc (Warner et al, 1999). Previous studies have shown that c-Myc was a repressor of P27 (Amendola et al, 2009) and P15 (Staller et al, 2001) and that down-regulation of c-Myc would up-regulate these cyclin-dependent kinase inhibitors-again, results supported by the current in vivo analysis of increased intracellular signaling in the TGF-β pathway. Studies have shown that the activation of cyclin-dependent kinase inhibitors would lead to increased levels of pRB, consistent with the findings in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Amla extract suppressed Wnt/β-catenin signalling by suppressing nuclear transport of β-catenin and downregulated β-catenin target proteins c-Myc and cyclin D1, which explains suppressed HCCSC proliferation and stem-ness (Amendola et al, 2009). Furthermore, efficacy of amla extracts was similar to cytotoxic drug FU.…”
Section: Fig 4 -Effect Of Methanol Extract Of Amla Seed (As) or Pulpmentioning
confidence: 97%